Understanding of Client’s Business in Audit Practice - Manko, N. F. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
One of the main requirements to audit tasks according to ISA is an understanding of the business entity’s nature. The process of business scrutiny is a lengthy and labor-consuming process because, apart from obtaining information from various sources, it involves its systematization and further analysis in order to make appropriate decisions. The role of business knowledge during the audit of a business entity is analyzed. A list of the essential issues which solution requires the necessary knowledge of the client’s business is given, the sources of obtaining the necessary information and factors that influence the auditor’s judgments at the phase of the task acceptance are considered. The specific nature of the audit activity requires the use of professional judgment at all audit phases, which necessitates heuristic methods of information analysis. The use of heuristic methods may contain a hidden threat – errors in the auditor’s judgment that can have significant effects for the auditor’s interim conclusions and the final judgment when forming the audit opinion regarding financial reporting. The article shows examples of errors in the auditor’s judgments that may arise at task acceptance and planning phases if the entity’s business is not fully understood. The issues which solutions require understanding of the business entity nature are grouped by phase of auditing on the basis of the author’s scrutiny and the existing audit practice. This study will provide a more thorough auditor’s approach to selecting resources for audit, obtaining high quality data about a business entity and its analysis; it will contribute in solutionsof theoretical and practical problems related with audit planning and performance, assessment of audit evidences, decision making to achieve the goal of audit: audit quality assurance.